Association of the non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio (NHHR) with COPD prevalence and all-cause mortality: a population-based study based on NHANES 2007–2016 - Yu Liu; Zheng Fan; Hongmei Ren; Cuixia Zheng (Frontiers in Medicine)
BackgroundThe non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio (NHHR) plays a potential role in metabolic and cardiovascular diseases. However, its association with chronic obstructive pulmonary disease (COPD) is not well-defined. Here, we aim to investigate the potential association of NHHR with both the prevalence of COPD and all-cause mortality among individuals with COPD.MethodsThis population-based NHANES (2007–2016) study utilized weighted statistical analyses. Multivariable logistic regression assessed the NHHR-COPD prevalence association, with restricted cubic spline (RCS) testing for non-linearity. The association between NHHR and all-cause mortality in COPD was evaluated using Cox proportional hazards models and Kaplan-Meier, with RCS testing for non-linearity. Subgroup and sensitivity analyses confirmed the findings’ reliability.ResultsThis study included 6349 participants, of whom 1271 were diagnosed with COPD. Participants in the highest NHHR tertile demonstrated 62% higher odds of COPD prevalence compared to those in the lowest tertile (OR = 1.62, 95% CI:1.11–2.39, P = 0.017). Results from RCS analysis indicated a nonlinear relationship between NHHR and the prevalence of COPD (P for nonlinear = 0.007), with the curve demonstrating an inverted L-shape. Over an average follow-up period of 93 months, 320 participants with COPD died. In the weighted Kaplan-Meier survival analysis, participants with COPD in the lower NHHR tertile demonstrated greater cumulative probability of all-cause mortality compared to higher tertiles (P < 0.001). Weighted multivariable Cox regression models revealed an inverse association between NHHR levels and COPD all-cause mortality, with the highest NHHR tertile showing 11% lower likelihood of COPD all-cause mortality relative to the lowest tertile (HR = 0.89, 95% CI:0.80–0.99, P = 0.027). In addition, RCS analysis demonstrated a significant negative linear association between NHHR levels and all-cause mortality in COPD patients (P for nonlinear = 0.081). Subgroup and sensitivity analyses further confirmed the associations of NHHR on both morbidity and all-cause mortality.ConclusionHigher NHHR levels were associated with increased COPD prevalence yet inversely correlated with all-cause mortality in COPD patients. These paradoxical associations underscore the need for COPD-specific lipid management strategies that balance disease progression and mortality risks.